ANALISIS PERSEDIAAN BAHAN BAKU TEPUNG TERIGU DENGAN MENGGUNAKAN METODE ECONOMIC ORDER QUANTITY (Studi Kasus di UD. Elza Putra Food) - Kuswardhani, Nita; Sapta, Muhammad Sadam Putra; Choiron, Miftahul (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Universitas Jember, 2024)
ABSTRACT The goals of research to determine the comparative results of inventory control of wheat flour raw material use Economic Order Quantity (EOQ) and conventional method, determine the reorder point and safety stock of wheat flour raw materials by UD. Elza Putra Food, and determine the difference inventory costs for wheat flour raw materials before and after use the Economic Order Quantity (EOQ) method at UD. Elza Putra Food The problems by UD. Elza Putra Food is a raw material control system use a conventionally based on previous orders and large amount of raw material stock so risk of running out of stock. The stages of research include field studies, literature studies, problem identification, conclusions and suggestions and analyzed using the Economic Order Quantity (EOQ) method. Applyed the EOQ method, total inventory costs can be minimized by Rp. 401,733, the number of orders is 118 zak more with an order frequency of 14 times, safety stock is 28 zak and the reorder point when raw materials remain is 41 zak. The conventional method incurred a total cost Rp. 1,340,161, order quantity 36 sacks with an order frequency 48 times, and reorder point if raw materials are 10 sacks without safety stock. The comparison results showed that the application of EOQ was 82 sacks higher in order quantity, 28 sacks of safety stock, 31 sacks of re-order points, and 34 times less ordering frequency.